Model of Work Motivation and Achievement: Knowledge Management and Work Experience at Water District Employees, Mukomuko District - Selvi Yona Sari; Zefriyenni Zefriyenni; Prima Sari Pascariati Kasman; Lusiana Lusiana; Desi Permata Sari (Institute of Computer Science (IOCS), 2021)
This study aims to determine and test how much influence knowledge management and work experience have on work performance with employee work motivation as an intervening variable for employees in Air Dikit District, Mukomuko Regency. The method of collecting data is through surveys and distributing questionnaires, with a sample of 36 respondents using all the population as samples. The analysis used is multiple linear regression and path analysis.The results of the data analysis concluded. There is a positive and significant influence between Knowledge Management on Employee Work Motivation at Air Dikit District Employees, Muko-Muko Regency. There is a positive and significant influence between Work Experience on Employee Work Motivation in Air District Employees. Dikit Muko-Muko Regency. There is a positive and significant influence between Knowledge Management on Work Performance in Air Dikit Subdistrict Employees, Muko-Muko Regency. There is a positive and significant influence between Work Experience on Work Performance in Air Dikit Subdistrict Employees. There is a positive and significant effect between Work Experience on Work Performance in Air Dikit District Employees, Muko-Muko Regency. Employee Work Motivation does not mediate Knowledge Management on Work Performance. Employee Work Motivation does not mediate Work Experience on Work Performance